Pengaruh Kepuasan Sebagai Variabel Intervening antara Media Sosial aan Niat Berkunjung Kembali Wisatawan Nusantara Generasi Milenial ke Bali - Ni Wayan Ria Agustini; I Nyoman Sudiarta; I Wayan Suardana (JURNAL MASTER PARIWISATA, 2022)
Social media has become the preferred method for exchanging information. The biggest social media users are millennials, who are tech-savvy. The rise of social media users can certainly influence the decision of tourists in visiting a destination. Tourists' interest in visiting again is considered as a result of satisfaction. Satisfaction can provide several benefits, one of which is to provide a good basis for repurchase or re-visit intention. The purpose of this study is to (1) analyze the influence of social media on satisfaction; (2) analyze the influence of social media on revisit intention; (3) analyze the effect of satisfaction on revisit intention; and (4) and analyze the influence of social media on revisit intention through satisfaction. This research was conducted by distributing online questionnaire using google form to 100 National Tourists as respondents. Sampling is executed the use of purposive sampling. Furthermore, the data will be analyzed using descriptive statistical analysis and using SmartPLS SEM (Structural Equation Modelling). The results showed that social media has a significantly influence National Tourist satisfaction, social media has a significantly influence National Tourist revisit intention to Bali, satisfaction has a significant influence on the revisit intention. On the indirect effect the results that indirectly social media has a significantly influence on the revisit intention thru satisfaction. Keywords: Sociallmedia, Satisfaction, Revisit Intention, Millennials.